Bevacizumab and anlotinib combination therapy acts via HIF-1α suppression to exert synergistic anti-angiogenic and anti-tumor effects in non-small cell lung cancer - Simayi, Nafeisha; Li, Jiaying; Hu, Junkai; Jia, Ning; Wan, Rongxue; Xie, Jinbiao; Huang, Wenhua (Frontiers in Immunology, 2025)
IntroductionTumor angiogenesis is required for the progression of non-small cell lung cancer (NSCLC), and anti-vascular endothelial growth factor (anti-VEGF) antibody bevacizumab and multitarget tyrosine kinase inhibitor anlotinib are anti-cancer treatment options, the combined effect of which in NSCLC remains unclear.MethodsA vascularized microfluidic chip was applied to model angiogenesis, together with in vitro assays, molecular analyses, and an in vivo mouse xenograft model, to evaluate therapeutic effects. Immunological changes were examined by assessing T-cell infiltration and cytokine levels, and the role of HIF-1α was validated using an inhibitor and an activator.ResultsBevacizumab plus anlotinib (B+A) inhibited angiogenesis, reducing vessel density to 10% of control values and also reducing diameter and green fluorescent protein (GFP) area ratio. B+A inhibited cell viability by 78%, colony formation by 90%, and invasion by 75% in NSCLC cell lines A549 and H1299; downregulated N-cadherin 5.34-fold, vimentin 6.46-fold, and α-SMA 4.35-fold; and upregulated E-cadherin 3.75-fold. The rates of apoptosis of A549 and H1299 cells were increased 3.85-fold. The phosphorylation of VEGFR2, PDGFRβ, and FGFR1 was also reduced. B+A reduced tumor volume 7.23-fold and weight 7.08-fold, decreased tumor cell density, and lowered Ki-67 expression in an in vivo mouse xenograft model. HIF-1α was inhibited in a time- and dose-dependent manner. Importantly, the combination therapy enhanced CD4+ and CD8+ T-cell infiltration, increased the production of pro-inflammatory cytokines such as IL-2, and reduced the expression of immunosuppressive factors such as IL-6, indicating an immunomodulatory effect that improved anti-tumor immunity.ConclusionHIF-1α inhibitor PX478 did not enhance the anti-tumor effects of B+A, but HIF-1α activator DMOG reversed them. In addition, the combination therapy enhanced CD4+ and CD8+ T-cell infiltration and increased pro-inflammatory cytokines. These findings highlight the therapeutic potential of combining anlotinib and bevacizumab for NSCLC treatment and identify HIF-1α as a key target.